REVIEW ON THE LEGALITY OF LEGAL ENTITY STATUS IN THE FOUNDATION BASED ON LAW NUMBER 28 OF 2004: THE PERSPECTIVE OF SIYASAH DUSTURIYAH, AND MASLAHAH MURSALAH - Muhammad Fakhrul Haq; M. Nur; Asma' Munifatussa'idah (Program Studi Hukum Keluarga Islam, 2023)
This research aims to examine the legalization of the legal entity status of Foundations in Indonesia after the enactment of Law No. 28 of 2004 with a review of Siyasah Dusturiyah and Maslahah Mursalah. This research used the approach method is the normative juridical in the form of library research, with a legal doctrine. The results of this in this research found that the legalization of the legal entity status of the Foundation had three stages, namely the establishment of the Foundation, the ratification of the foundation deed, and the announcement of the Foundation as a legal entity. Then Law No. 28 of 2004 concerning the legal entity legalization system of Foundations after being tested in a material juridical manner, article by article, is considered to have met the eligibility standards in state administration and has complied with the legal principles in the AAUPL. However, based on the study of Siyasah Dusturiyah theory with eight legal principles, there are two principles that are not contained in the Foundation Law, namely the principle of monotheism and the principle of social balance. And likewise, based on the theory of Maslahah Mursalah, the Foundation Law does not fulfill the principle because there are more harm that result from the benefits obtained.